Unpacking the Black Box Between Entrepreneurial Leadership and Innovation Performance: The Role of Digital Orientation - Susanti Dwi Ilhami; Damayanti Damayanti (MANAJEMEN, 2025)
The purpose of this study is to explore the role of digital orientation as a moderation in the influence of entrepreneurial leadership and innovation performance on culinary UMKM in Rembang Regency. The research that has been conducted uses the concept of explanatory research as a reference in accordance with the objectives of the study. The sampling technique used is the purposive sampling technique with 82 business owners. The data analysis method implements SEM-PLS. The results of the study revealed that entrepreneurial leadership has no significant influence on innovation performance. In addition, further findings indicate that digital orientation is unable to moderate the influence of entrepreneurial leadership on innovation performance. Research has contributed widely to the understanding of business owners behavior in an effort to improve innovation performance with entrepreneurial leadership and strengthened by digital orientation.